 It is currently 19 Jul 2019, 10:56 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here. # The functions f and g are defined as f(x) = 2x – 3 and g(x)  Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:
Founder  Joined: 18 Apr 2015
Posts: 7386
Followers: 123

Kudos [?]: 1448 , given: 6583

The functions f and g are defined as f(x) = 2x – 3 and g(x) [#permalink]
Expert's post 00:00

Question Stats: 100% (00:45) correct 0% (00:00) wrong based on 4 sessions
The functions f and g are defined as f(x) = 2x – 3 and g(x) = x + $$\frac{3}{2}$$. For what value of y is f(y) = g(y – 3) ?

(A) 1

(B) $$\frac{3}{2}$$

(C) 2

(D) 3

(E) 5
[Reveal] Spoiler: OA

_________________ GRE Instructor Joined: 10 Apr 2015
Posts: 2162
Followers: 64

Kudos [?]: 1975  , given: 19

Re: The functions f and g are defined as f(x) = 2x – 3 and g(x) [#permalink]
1
KUDOS
Expert's post
Carcass wrote:
The functions f and g are defined as f(x) = 2x – 3 and g(x) = x + $$\frac{3}{2}$$. For what value of y is f(y) = g(y – 3) ?

(A) 1

(B) $$\frac{3}{2}$$

(C) 2

(D) 3

(E) 5

If f(x) = 2x – 3, then f(y) = 2y – 3

If g(x) = x + $$\frac{3}{2}$$, then g(y – 3) = y – 3 + $$\frac{3}{2}$$

We want: f(y) = g(y – 3)

We can rewrite this equation as: 2y – 3 = y – 3 + $$\frac{3}{2}$$

Add 3 to both sides to get: 2y = y + $$\frac{3}{2}$$

Subtract y from both sides to get: y = $$\frac{3}{2}$$

Cheers,
Brent
_________________

Brent Hanneson – Creator of greenlighttestprep.com  Re: The functions f and g are defined as f(x) = 2x – 3 and g(x)   [#permalink] 14 May 2019, 11:37
Display posts from previous: Sort by

# The functions f and g are defined as f(x) = 2x – 3 and g(x)  Question banks Downloads My Bookmarks Reviews Important topics Powered by phpBB © phpBB Group Kindly note that the GRE® test is a registered trademark of the Educational Testing Service®, and this site has neither been reviewed nor endorsed by ETS®.